1987
DOI: 10.1002/1097-0142(19870615)59:12<2016::aid-cncr2820591208>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cranial irradiation in adenocarcinoma of the lung a possible role

Abstract: Seventy-eight patients with modified Stage II or Stage IIIM0 adenocarcinoma of the lung were evaluated retrospectively with regard to the impact of prophylactic cranial irradiation (PCI) (30 Gy in 15 fractions) in preventing central nervous system (CNS) metastases. Twenty patients received PCI and 58 did not. There were no significant differences between these groups with respect to age, sex, stage, or median survival (17.4 months with PCI versus 16.9 months without PCI; P = 0.6). One (5%) of 20 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…The more recent RTOG-0214 trial (14) demonstrated a significant decrease in the risk of BM in patients with locally advanced NSCLC. Several other nonrandomised/retrospective studies demonstrated a significant benefit in a reduction of incidence of BM (11,16,19).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The more recent RTOG-0214 trial (14) demonstrated a significant decrease in the risk of BM in patients with locally advanced NSCLC. Several other nonrandomised/retrospective studies demonstrated a significant benefit in a reduction of incidence of BM (11,16,19).…”
Section: Resultsmentioning
confidence: 93%
“…The largest RTC reported no significant increase in DFS for patients with NSCLC after PCI; DFS rates reported at 1 year were 56.4% and 51.2% for the PCI and observation arms, respectively (p=0.11) (14). A retrospective review by Jacobs et al also demonstrated no survival benefit with the use of PCI (19).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A study conducted by Vuong et al [196] found males had a higher prevalence of brain metastasis than females (p<0.001), but the frequency of brain metastasis in a study conducted by Pickren et al [131] was not different (8.8% in men and 8.7% in women). Race has not been associated with brain metastasis [131] and was not included as a covariate in the majority of studies [8,9,185,187,[189][190][191][192][193][194][195][197][198][199][200][201][202][203][204]. Breast cancer is the most common source of brain metastasis for women [5].…”
Section: Risk Factorsmentioning
confidence: 99%